Pemberdayaan Literasi Sosial Berbasis Komunitas Untuk Meningkatkan Kemandirian Ekonomi Bahan Pangan Lokal - Abd. Hamid Isa; Zulkarnain Anu; Muhammad Ibrahim (CERED Indonesia Publishing, 2026)
The strategy and effort to build villages accommodate village activists to create collective learning spaces in village resource governance. Village initiatives and capabilities in managing existing resources in their areas are the basic capital to create strong, advanced, and independent villages. Literacy in the form of information technology is a learning tool that can bridge village activists in various regions through relevant and sustainable community service program interventions to reduce and minimize the presence of poor communities in villages. Gorontalo Province is ranked 6th out of 10 regions with the highest number of poor people in September 2023 (BPS, January 2024), with a poor population of 15.41 percent and Central Sulawesi is ranked 10th with a percentage of poor people of 12.18 percent. The distribution of poor population areas is found to be in the Tomini Bay area. The Thematic KKN Program by LPPM UNG in 2025 is oriented to improve the quality of the number of community service of UNG lecturers. Providing solutions to partner problems with a holistic approach based on multidisciplinary research that has been implemented and is able to be effective for the priority scale of community development in the 3T region as stated in Presidential Decree No. 63 of 2020 and based on BPS data in 2021. The target of the community-based social literacy empowerment program to support the development of local food economic independence through this Thematic KKN program is the realization of a community that has good knowledge and understanding of social literacy as part of the learning process and has skills that are an effort to improve welfare through economic independence and local food security of the community. The type of literacy development developed is a community-based potential that is worth exploring (village) that is available and has comparative advantages and competitive advantages both economically, socially and environmentally that can be produced and marketed in order to create community economic independence through a local food security program.